Phase-change composite heat and energy storage material and preparation method thereof

Through the preparation of composite phase change materials, the synergistic effect of porous silica and nano Al2O3 is used to solve the problems of high supercooling and phase separation of phase change heat storage materials, and efficient heat storage and rapid response are achieved, which is suitable for building heating and industrial waste heat recovery.

CN120424622APending Publication Date: 2025-08-05GUANGXI COLLEGE OF WATER RESOURCES & ELECTRIC POWER

Patent Information

Application Number
CN202510321452.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-08-05

AI Technical Summary

Technical Problem

The existing phase change heat storage materials have problems such as high supercooling, phase separation, insufficient latent heat in phase change and poor comprehensive performance, which is difficult to meet the needs of efficient heat storage and heat management such as building heating and industrial waste heat recovery.

Method used

The composite design of sodium acetate trihydrate, disodium hydrogen phosphate dodecyl water, porous silica, nano Al2O3, expanded graphite and borax is used to prepare phase-change composite heat storage materials through vacuum impregnation, stirring, grinding and cooling. The capillary action of porous silica is used to prevent phase separation. Nano Al2O3 promotes rapid nucleation, expanding graphite improves thermal conductivity, and borax maintains material stability.

Benefits of technology

Significantly reduce the supercooling degree, solve the problem of phase separation, improve the latent heat and thermal conductivity of phase change, realize high energy density heat storage and rapid response, extend the life of the material, and is suitable for building heating, industrial waste heat recovery and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120424622A_ABST
    Figure CN120424622A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of phase change heat storage materials, and particularly relates to a phase change composite heat storage and energy storage material and a preparation method thereof. The phase-change composite heat and energy storage material comprises the following raw material components: sodium acetate trihydrate, disodium hydrogen phosphate dodecahydrate, porous silicon dioxide, nano Al2O3, expanded graphite, borax, polyacrylamide and the balance of water. The preparation method of the material comprises the following steps: S1, heating sodium acetate trihydrate to a molten state, and dipping into porous silicon dioxide; s2, adding borax, nano Al2O3, disodium hydrogen phosphate dodecahydrate, polyacrylamide and water, and stirring for dissolving; s3, adding expanded graphite, and grinding; and S4, cooling to obtain the product. The invention aims to solve the key problems of high supercooling degree, phase separation, insufficient phase change latent heat, poor comprehensive performance and the like of the existing phase change heat storage material, and a new material meeting the requirements of building heating, industrial waste heat recovery, solar heat storage and other fields on efficient heat storage and heat management is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of phase change thermal storage materials, and in particular relates to a phase change composite thermal storage material and a preparation method thereof. Technical Background

[0002] Phase change materials (PCMs) are substances that undergo phase transitions with temperature, absorbing or releasing large amounts of heat in the process. PCMs are widely used in thermal storage, with organic and inorganic materials being the primary research areas. Organic PCMs, such as paraffin, offer stable performance and are largely immune to supercooling and phase separation issues, but they have low heat storage capacity per unit volume. n-Octadecane, a component of paraffin, has a low density, making it difficult to meet the thermal storage efficiency requirements for scenarios such as large-scale industrial waste heat recovery and heating high-energy-consuming buildings.

[0003] Inorganic phase-change thermal storage materials, such as sodium acetate trihydrate and disodium hydrogen phosphate dodecahydrate, offer advantages in terms of heat storage per unit volume and thermal conductivity, but they also have significant drawbacks. Sodium acetate trihydrate is prone to phase separation after repeated thermal cycles, impacting material performance and service life. Disodium hydrogen phosphate dodecahydrate also has a high degree of supercooling, hindering efficient energy storage and rapid release, reducing system energy efficiency.

[0004] Chinese patent CN115368876A discloses a disodium hydrogen phosphate dodecahydrate composite phase-change thermal storage material and its preparation method. The material is prepared by uniformly mixing disodium hydrogen phosphate dodecahydrate, potassium hydroxide, and water and heating until completely melted. The material undergoes 100 melting-solidification cycles without phase separation, maintaining a supercooling degree between 0.7°C and 5.4°C. When the ambient temperature is above approximately 42°C, the material melts with endothermic heat, while when the ambient temperature is below approximately 42°C, the material solidifies with exothermic heat. Two new substances, K2HPO4 and NaOH, are generated in the composite phase-change thermal storage material. These two substances act as nucleating agents, promoting solidification and thereby reducing the supercooling degree of the composite phase-change material. The disodium hydrogen phosphate dodecahydrate composite phase-change thermal storage material has low production costs and is suitable for mass production. It can be used in rural areas, such as earthen kangs, coal stoves, and radiant floor heating. In this patent, although the performance is improved by adding potassium hydroxide and the like, the degree of supercooling reduction is limited, the increase in the latent heat of phase change is not significant, and the performance stability in complex environments has not been fully studied.

[0005] Patent CN101186806A discloses a phase change thermal storage material, which is mainly composed of the following materials in the following mass ratio: 85-98 parts of sodium acetate trihydrate, 1-10 parts of carboxymethyl cellulose, 0.5-3.5 parts of magnesium chloride hexahydrate, 0.1-2.5 parts of sodium carboxymethyl cellulose, and 0-10ppm of nano-carbon powder. The raw materials required for the phase change thermal storage material are abundant and low in price; the phase change thermal storage capacity is large (greater than 280MJ / m3 ), high thermal conductivity (greater than 0.8W / m·K); a phase transition temperature of 54°C to 60°C, which is advantageous for recovering heat from air conditioner condensers and other waste heat recovery applications; and a low degree of subcooling (3°C to 5°C), which is extremely beneficial for releasing the required heat. However, the phase separation problem in this patent remains unresolved, affecting long-term performance. Summary of the Invention

[0006] The present invention provides a phase-change composite thermal energy storage material, which aims to solve key problems of existing phase-change thermal energy storage materials, such as high supercooling, phase separation, insufficient phase change latent heat and poor overall performance.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] A phase-change composite heat and energy storage material comprises the following raw materials, calculated by weight percentage: 75% to 85% sodium acetate trihydrate, 3% to 5% disodium hydrogen phosphate dodecahydrate, 2% to 4% porous silicon dioxide, 1% to 3% nano-Al2O3, 5% to 8% expanded graphite, 0.5% to 1.5% borax, 0.01% to 0.3% polyacrylamide, and the balance being water.

[0009] Preferably, the particle size of the porous silica is 10 to 50 nm.

[0010] Preferably, the nano-Al2O3 is in granular form with a particle size of 20 to 50 nm.

[0011] Preferably, the particle size of the expanded graphite is less than 10 μm.

[0012] In the above raw material formula of the present invention, sodium acetate trihydrate (NaCH3COO·3H2O) is used as the main phase change material to provide high phase change latent heat (≥220kJ / kg), which is a key component for achieving efficient heat storage; disodium hydrogen phosphate dodecahydrate (Na2HPO4·12H2O) can assist in regulating the phase change temperature, stabilizing the phase change temperature in the range of 45°C to 55°C to meet the requirements of various working conditions; the capillary effect of the porous structure of porous silica can effectively adsorb the liquid phase, prevent sodium acetate trihydrate from phase separation during the thermal cycle, and ensure the stability of material performance; nano-Al2O3 is used as an efficient nucleating agent during the phase change process. The process promotes rapid nucleation, reduces the supercooling degree to 1℃~2℃, and improves the efficiency of energy storage and release; expanded graphite can significantly improve the overall thermal conductivity of the material, making its thermal conductivity ≥2.0W / m·K, accelerating heat transfer and improving thermal conversion efficiency; borax, as a pH buffer, inhibits the hydrolysis of sodium acetate, maintains the chemical stability of the material, and extends its service life; polyacrylamide, as a thickener, can accurately adjust the viscosity of the material, enhance the operability of the material during preparation and application, and ensure the uniformity and stability of the material; water, as a solvent, is deeply involved in the formation of the material's microstructure and the regulation of its properties, and plays an important role as a dispersion and reaction medium in the material system.

[0013] Another object of the present invention is to provide a method for preparing the phase-change composite thermal energy storage material, comprising the following steps:

[0014] S1. Sodium acetate trihydrate is heated to a molten state, and then, under vacuum conditions, the molten sodium acetate trihydrate is impregnated into the porous silica, so that the sodium acetate trihydrate fully fills the pores of the porous silica to form a stable composite structure and enhance the material's resistance to phase separation;

[0015] S2. Borax, nano-Al2O3, disodium hydrogen phosphate dodecahydrate, polyacrylamide, and water were sequentially added to the mixture A and stirred until completely dissolved to form a colloidal solution to obtain a mixture A; the ingredients were fully mixed and interacted to form a uniform and stable mixture, laying the foundation for subsequent performance improvement;

[0016] S3. Expanded graphite was added to the mixture A in batches and ground to ensure that the expanded graphite was evenly dispersed in the material system to obtain a mixture B; by evenly dispersing the expanded graphite in the material system, the thermal conductivity of the material can be effectively improved to ensure that heat can be quickly transferred;

[0017] S4. Cooling the ground material to form a stable crystal structure, controlling the cooling process, optimizing the microstructure of the material, and further improving the performance stability and phase change efficiency of the material.

[0018] Preferably, in step S1, the vacuum condition is a vacuum degree ≤ 0.1 MPa.

[0019] Preferably, in step S2, the stirring temperature is 60-80° C. and the stirring time is 3-5 hours.

[0020] Preferably, in step S3, the grinding speed is 300-500 rpm and the grinding time is 1-3 hours.

[0021] Preferably, in step S3, the grinding is performed by ball milling.

[0022] Preferably, in step S3, the batch addition comprises adding the expanded graphite to the mixture A in three batches, 20%, 30%, and 50% of the total mass, and stirring at 100-500 rpm for 10-30 minutes after each addition to ensure sufficient dispersion before adding the next batch. This operation can avoid agglomeration of the expanded graphite caused by adding it all at once and improve its uniformity in the material system.

[0023] Preferably, in step S4, the cooling rate is 0.5-1.5°C / min, and the temperature is lowered to -10-0°C.

[0024] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0025] 1. Significantly reduced supercooling: The present invention uses nano-Al2O3 as a nucleating agent, and the supercooling degree of the prepared material is between 0.8℃ and 2.0℃, which is lower than that of some existing materials. The phase change is stable and efficient, effectively reducing energy loss during the supercooling process.

[0026] 2. Completely solve the phase separation problem: The present invention utilizes the capillary adsorption effect of porous silica to effectively prevent the separation of sodium acetate crystals and the water phase. The latent heat retention rate after thermal cycling is high, which greatly extends the service life of the material.

[0027] 3. High energy density: Through reasonable composition, it can store and release more heat, increase volume heat storage capacity, meet high energy storage needs, and have higher application value in building heating, industrial waste heat recovery and other fields.

[0028] 4. Fast thermal response: Adding expanded graphite, heat transfer is faster, heat release rate is increased, it can quickly respond to thermal demand and improve energy utilization efficiency.

[0029] 5. Long life and low cost: The material cost is reduced. By optimizing the composition and preparation process, the material performance is stable and the service life is ≥10 years, with good economic benefits and application prospects.

[0030] 6. Preparation process advantages: The preparation method combines existing processes and optimizes parameters. The operation is relatively simple and can be mass-produced under conventional equipment and conditions, thus reducing production costs and facilitating industrial promotion and application.

[0031] 7. The present invention uses innovative material composite design and optimized preparation process to prepare a new type of composite phase change thermal storage material with excellent comprehensive performance, which meets the needs of efficient heat storage and thermal management in fields such as building heating, industrial waste heat recovery, and solar thermal storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a SEM image of the microstructure of the material obtained in Example 1, showing the anchoring effect of porous SiO2 on sodium acetate;

[0033] Figure 2 1000 thermal cycle performance test comparison chart of Examples 1 to 3 and Comparative Examples 1 to 3;

[0034] Figure 3 The DSC curves of Examples 1 to 3 and Comparative Examples 1 to 3 are compared with the phase change thermal performance. DETAILED DESCRIPTION

[0035] In order to better present the present invention, it is illustrated through specific implementation cases. These implementation cases belong to the protection scope of the present invention but do not limit the protection scope of the present invention.

[0036] Example 1

[0037] A phase-change composite heat and energy storage material comprises 800 g of sodium acetate trihydrate, 40 g of disodium hydrogen phosphate dodecahydrate, 30 g of porous SiO2, 20 g of nano-Al2O3, 60 g of expanded graphite, 10 g of borax, 0.1 g of polyacrylamide, and 39.9 g of deionized water.

[0038] In this embodiment, the method for preparing the phase change composite thermal energy storage material includes the following steps:

[0039] S1. Sodium acetate trihydrate is heated to a molten state, and then the molten sodium acetate trihydrate is impregnated into the porous silica under vacuum conditions of a vacuum degree ≤ 0.1 MPa;

[0040] S2. Borax, nano-Al2O3, disodium hydrogen phosphate dodecahydrate, polyacrylamide, and deionized water were sequentially added to the mixture A and stirred until completely dissolved to form a colloidal solution. The temperature was controlled at 70 ° C and stirred for 4 hours to obtain a mixture A;

[0041] S3. Expanded graphite was added to the mixture A in batches and ball milled at a speed of 400 rpm for 2 hours to ensure that the expanded graphite was uniformly dispersed in the material system to obtain a mixture B;

[0042] S4. Cooling the ground material to -5°C at a rate of 1°C / min.

[0043] Example 2

[0044] A phase-change composite heat and energy storage material comprises 750 g of sodium acetate trihydrate, 50 g of disodium hydrogen phosphate dodecahydrate, 40 g of porous SiO2, 30 g of nano-Al2O3, 80 g of expanded graphite, 15 g of borax, 2 g of polyacrylamide, and 33 g of distilled water.

[0045] In this embodiment, the method for preparing the phase change composite thermal energy storage material includes the following steps:

[0046] S1. Sodium acetate trihydrate is heated to a molten state, and then the molten sodium acetate trihydrate is impregnated into the porous silica under vacuum conditions of a vacuum degree ≤ 0.1 MPa;

[0047] S2. Borax, nano-Al2O3, disodium hydrogen phosphate dodecahydrate, polyacrylamide, and distilled water were sequentially added to the mixture A and stirred until completely dissolved to form a colloidal solution. The temperature was controlled at 65 ° C and stirred for 5 hours to obtain a mixture A;

[0048] S3. Expanded graphite was added to the mixture A in batches and ball milled at a speed of 300 rpm for 3 hours to ensure that the expanded graphite was uniformly dispersed in the material system to obtain a mixture B;

[0049] S4. Cooling the ground material to 0°C at a rate of 0.5°C / min.

[0050] Example 3

[0051] A phase-change composite heat and energy storage material comprises 850 g of sodium acetate trihydrate, 30 g of disodium hydrogen phosphate dodecahydrate, 20 g of porous SiO2, 10 g of nano-Al2O3, 50 g of expanded graphite, 5 g of borax, 3 g of polyacrylamide, and 32 g of distilled water.

[0052] In this embodiment, the method for preparing the phase change composite thermal energy storage material includes the following steps:

[0053] S1. Sodium acetate trihydrate is heated to a molten state, and then the molten sodium acetate trihydrate is impregnated into the porous silica under vacuum conditions of a vacuum degree ≤ 0.1 MPa;

[0054] S2. Borax, nano-Al2O3, disodium hydrogen phosphate dodecahydrate, polyacrylamide, and distilled water were sequentially added to the mixture A and stirred until completely dissolved to form a colloidal solution. The temperature was controlled at 80 ° C and stirred for 3 hours to obtain a mixture A;

[0055] S3. Expanded graphite was added to the mixture A in batches and ball milled at a speed of 500 rpm for 1 hour to ensure that the expanded graphite was uniformly dispersed in the material system to obtain a mixture B;

[0056] S4. The ground material is cooled at a rate of 1.5°C / min to -10°C.

[0057] Comparative Example 1

[0058] The method is basically the same as Example 1, except that the raw materials do not include 30 g of porous SiO2 and 20 g of nano-Al2O3, but are replaced with an equal amount of diatomaceous earth (porosity ≤ 50%), and the amounts of other ingredients remain unchanged.

[0059] Comparative Example 2

[0060] The method is basically the same as Example 1, except that the raw material does not include 30 g of porous SiO2, but is replaced by an equal amount of diatomaceous earth (porosity ≤ 50%), and the amounts of other ingredients remain unchanged.

[0061] Comparative Example 3

[0062] The method is basically the same as Example 1, except that the raw material does not include 20 g of nano-Al2O3, but is replaced by an equal amount of diatomaceous earth (porosity ≤ 50%), and the amounts of other ingredients remain unchanged.

[0063] Performance Testing

[0064] 1. The phase transition temperature and supercooling degree of the materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were tested using a differential scanning calorimeter (DSC).

[0065] 2. The phase change latent heat of the materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested using a differential scanning calorimeter (DSC).

[0066] 3. The thermal conductivity of the materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested using a transient planar heat source method (Hot Disk).

[0067] 4. Industrial waste heat recovery experiment

[0068] 4.1 Experimental setup

[0069] (1) A simulated industrial waste heat system is used, including an electric heating waste heat generator (power adjustable range 0-5kW), a shell and tube heat exchanger (heat exchange area 1.2m 2 ), circulating water pump (flow rate 0~10L / min), temperature sensor (accuracy ±0.1℃), flow meter (accuracy ±1%), data acquisition system (recording temperature, flow rate and heat flow data).

[0070] (2) The prepared phase change composite thermal storage material was encapsulated in a customized thermal storage unit (size 30 cm × 30 cm × 5 cm, internal filling material thickness 3 cm) and integrated into the thermal storage side of the heat exchanger.

[0071] (3) Constant temperature water (simulating industrial waste heat, the temperature is set to 45℃±0.5℃) is introduced into the heat source side, and the flow rate is adjusted to 2L / min.

[0072] 4.2 Experimental Conditions

[0073] (1) Waste heat input stage: 45°C hot water is continuously introduced into the heat source side for 2 hours to simulate the stable output of industrial waste heat.

[0074] (2) Heat storage stage: The heat storage material absorbs the residual heat, and the phase change process of the material is monitored in real time through temperature sensors (arranged at the inlet and outlet and inside the heat storage unit) until the material is completely melted (the temperature reaches 54℃±1℃).

[0075] (3) Heat release stage: Turn off the heat source, start the cold side circulating water (initial temperature 15℃±1℃, flow rate 2L / min), and record the process of the thermal storage material releasing heat to the cold side until the material temperature drops below the phase change point (≤45℃).

[0076] 4.3 Repeatability and Verification

[0077] (1) Each experiment was repeated three times, and the average value was taken as the final result.

[0078] (2) The control group used traditional phase change materials (such as pure sodium acetate trihydrate-based materials) to conduct the same experiment and compare the differences in recovery efficiency.

[0079] (3) A high-precision heat flow meter (model: HFM-100, accuracy ±0.5%) was used to verify the heat transfer data to ensure the reliability of the calculation results.

[0080] 4.4 Key parameter recording

[0081] (1) Real-time temperature and flow data of the heat source side and the cold side (sampling frequency 1Hz).

[0082] (2) Phase change time, temperature change curve and latent heat release rate of thermal storage materials.

[0083] (3) The temperature distribution on the material surface was observed using a thermal imager (FLIR T1030sc) to ensure uniform heat release.

[0084] (4) Through the above steps, the waste heat recovery efficiency can be quantitatively obtained, and the performance advantages of the material of the present invention in the industrial waste heat recovery scenario can be verified.

[0085] 5. See the table below for test results.

[0086] Treatment group Phase transition temperature / ℃ Subcooling degree / ℃ Latent heat of phase change / kJ / kg Thermal conductivity / W / m·K Waste heat recovery efficiency / % Example 1 54±1 1.0 252 2.5 88% Example 2 51±1 1.5 238 2.1 82% Example 3 52±1 1.2 245 2.3 86% Comparative Example 1 53±2 4.8 195 1.2 65% Comparative Example 2 51±1 3.5 210 1.6 72% Comparative Example 3 52±1 2.9 225 1.8 78%

[0087] First, overall, the phase change composite thermal storage materials of Examples 1 to 3 of the present invention exhibit significant comprehensive performance advantages compared to Comparative Examples 1 to 3, especially highlighting the efficient thermal management capabilities in industrial waste heat utilization.

[0088] Secondly, by comparing the data of Example 1 and Comparative Examples 1 to 3, it can be seen that: in Comparative Example 1, when porous SiO2 and nano-Al2O3 are not added, all indicators are affected to a certain extent, especially the supercooling is greatly increased, while the latent heat of phase change, thermal conductivity, and waste heat recovery efficiency are greatly reduced; Comparative Examples 2 to 3 respectively add porous SiO2 and nano-Al2O3 on the basis of Comparative Example 1, and all indicators are improved to a certain extent, but none of them can reach the effect of Example 1, and in terms of the four indicators of supercooling, latent heat of phase change, thermal conductivity, and waste heat recovery efficiency, the effect of Example 1 relative to Comparative Example 1 is greater than the sum of the effects of Comparative Examples 2 and 3 relative to Comparative Example 1. It can be seen that the mixed effect of porous SiO2 and nano-Al2O3 reflects the synergistic effect between the two due to the effect of using them alone. This is because:

[0089] (1) Supercooling: Nano-Al2O3 as a nucleating agent effectively promotes the rapid nucleation of the phase change process and reduces energy loss; while porous SiO2 inhibits the flow segregation of liquid phase change materials through the capillary adsorption of nano-pores, stabilizes the solid-liquid interface, and reduces the supercooling phenomenon caused by local uneven composition.

[0090] (2) Phase change latent heat: The pore structure of porous SiO2 effectively anchors sodium acetate trihydrate. This efficient composite with the main phase change material improves the energy storage density and can prevent phase separation after thermal cycling. Nano-Al2O3 promotes uniform nucleation, reduces the latent heat dissipation caused by incomplete crystallization or local overheating, and further improves the latent heat utilization efficiency.

[0091] (3) Thermal conductivity: The porous SiO2 structure optimizes the heat flow distribution inside the material, reduces thermal resistance, and assists expanded graphite in building a continuous thermal network. Nano-Al2O3, with its own high thermal conductivity, acts as a thermal "bridge" to accelerate local heat transfer and synergizes with expanded graphite to improve the overall thermal conductivity.

[0092] (4) Waste heat recovery efficiency: Porous SiO2 anchors the main phase change material, reducing structural degradation during thermal cycles and ensuring long-term stable waste heat recovery efficiency; nano-Al2O3 reduces the supercooling degree to 1.0°C, allowing heat to be released quickly near the phase change point, shortening the system response time and improving the waste heat recovery rate.

[0093] In summary: Through the synergistic effect of porous SiO2 and nano-Al2O3, the phase change material of the present invention solves the problems of high supercooling and phase separation of traditional inorganic phase change materials. At the same time, combined with the high thermal conductivity of expanded graphite, it breaks through the existing technical bottlenecks in energy storage density, thermal response speed and long-term stability, and is suitable for high-demand scenarios such as building heating and industrial waste heat recovery.

[0094] 6.1000 times thermal cycle performance test experiment: The materials obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to 1000 heating-cooling cycles. The latent heat retention rate and supercooling degree were measured after every 100 cycles. The test results are as follows: Figure 2 As shown. Figure 2 It can be seen that:

[0095] (1) Latent heat retention: The latent heat retention of Examples 1 to 3 is still higher than 90% after 1000 cycles (the initial latent heat of Example 1 is 252 kJ / kg, and the latent heat decay rate after 1000 cycles is <10%), indicating that the material effectively suppresses the phase separation phenomenon through the anchoring effect of porous silica on the main phase change material and the uniform nucleation effect of nano-Al2O3, thereby ensuring long-term cycle stability. The latent heat retention of Comparative Example 1 (without the addition of porous SiO2 and nano-Al2O3) decreases significantly with the number of cycles (initial latent heat 195 kJ / kg, latent heat value ≤150 kJ / kg after 1000 cycles), verifying that the lack of key components leads to aggravated phase separation and deterioration of energy storage performance.

[0096] 7. (2) Supercooling stability: The supercooling of Examples 1 to 3 is always stable in the range of 1.0 to 1.5°C (the initial supercooling of Example 1 is 1.0°C, and it only rises to 1.3°C after 1000 cycles), which proves that nano-Al2O3 as an efficient nucleating agent can continuously promote the rapid nucleation of the phase change process and reduce energy loss. The supercooling of Comparative Example 1 rises from the initial 4.8°C to 6.2°C after 1000 cycles, indicating that the traditional material loses control of supercooling due to structural degradation and composition segregation, affecting the thermal management efficiency. 3 to 10 mg of the materials obtained in Examples 1 to 3 and Comparative Examples 1 to 3 are weighed on a balance and placed in a crucible. The heating rate is set to 10°C / min, the temperature range is 20 to 100°C, and 30 mL / min of nitrogen is used as the protective gas. The sample and the reference empty crucible are symmetrically placed in a differential scanning calorimeter (DSC), and the DSC curve of the composite phase change material is measured, as shown below. Figure 3As shown. Figure 3 It can be seen that:

[0097] (1) Phase transition temperature and peak shape characteristics: The endothermic peaks (melting) and exothermic peaks (solidification) of Examples 1 to 3 are all located in the range of 45 to 55°C (the phase transition temperature of Example 1 is 54±1°C), and the peak shapes are sharp and symmetrical, indicating that the material phase transition process is efficient and the temperature range is stable, suitable for building heating and industrial waste heat recovery scenarios. The endothermic peak and exothermic peak of Comparative Example 1 are separated by a large distance (phase transition temperature is 53±2°C), and the peak shape is broad and asymmetrical, reflecting the increased supercooling (4.8°C) and the unevenness of the phase transition process.

[0098] (2) Phase Change Latent Heat and Energy Storage Density: The peak area of the DSC curve of Example 1 is significantly greater than that of Comparative Example 1 (latent heat of 252 kJ / kg for Example 1 and 195 kJ / kg for Comparative Example 1), indicating that the synergistic effect of porous silica and nano-Al2O3 improves the crystallization efficiency and energy storage density of the main phase change material. The peak areas of Comparative Examples 1 to 3 decrease with the degree of loss of key components, verifying that the thermal performance of the phase change material deteriorates when porous SiO2 and nano-Al2O3 are not combined.

[0099] (3) Verification of supercooling: The temperature difference (supercooling) between the endothermic peak and the exothermic peak of Example 1 is 1.0°C, while the temperature difference of Comparative Example 1 is 4.8°C, which directly confirms the inhibitory effect of nano-Al2O3 as a nucleating agent on the supercooling phenomenon and the stabilizing effect of porous SiO2 on the microstructure of the material.

[0100] 8. Building heating simulation experiment

[0101] A temperature controlled cabin (1m 3 ) Integrate the phase change thermal storage plate of Example 1 of the present invention: during the day, the material is heated to 60°C through the electric heating film to melt and store heat (simulating solar energy or low-valley electricity heat storage), and at night, the heat source is turned off and forced convection heat dissipation is started (wind speed 0.5m / s) to simulate winter heating needs.

[0102] Experimental results show that the material in Example 1 can continuously release latent heat when cooled to 15°C, maintaining a stable cabin temperature of 18±2°C for over 6 hours, with a supercooling degree of only 1.0°C (according to Example 1, traditional materials are ≥5°C), ensuring rapid heat release. After 50 charge and discharge cycles, the material's phase change latent heat decay rate was less than 3%, with no structural cracking or leakage. This demonstrates its advantages of efficient heat storage, precise temperature control, and long life in intermittent heating scenarios, making it suitable for low-carbon heating scenarios such as passive buildings and floor heating systems.

[0103] The above description is a further detailed description of the present invention in conjunction with specific / preferred embodiments, and the specific implementation of the present invention should not be considered to be limited to these descriptions. Those skilled in the art of the present invention may make various substitutions or modifications to the described embodiments without departing from the scope of the present invention, and such substitutions or modifications should be considered to fall within the scope of protection of the present invention.

Claims

1. A phase-change composite thermal energy storage material, characterized in that: The raw material composition is as follows: 75% to 85% of sodium acetate trihydrate, 3% to 5% of disodium hydrogen phosphate dodecahydrate, 2% to 4% of porous silicon dioxide, 1% to 3% of nano-Al2O3, 5% to 8% of expanded graphite, 0.5% to 1.5% of borax, 0.01% to 0.3% of polyacrylamide, and the balance is water.

2. The phase change composite thermal energy storage material according to claim 1, characterized in that: The particle size of the porous silicon dioxide is 10 to 50 nm.

3. The phase change composite thermal energy storage material according to claim 1, characterized in that: The particle size of the nano-Al2O3 is 20-50nm.

4. The phase-change composite thermal energy storage material according to claim 1, wherein: The particle size of the expanded graphite is less than 10 μm.

5. A method for preparing the phase change composite thermal energy storage material according to claim 1, characterized in that: The following steps are involved: S1. Sodium acetate trihydrate is heated to a molten state, and then the molten sodium acetate trihydrate is impregnated into the porous silica under vacuum conditions; S2. Borax, nano-Al2O3, disodium hydrogen phosphate dodecahydrate, polyacrylamide, and water were sequentially added to the above system and stirred until completely dissolved to form a colloidal solution to obtain a mixture A; S3. Expanded graphite was added to the mixture A in batches and ground to uniformly disperse the expanded graphite in the material system to obtain a mixture B; S4. Cooling the mixture B to obtain.

6. The method for preparing the phase-change composite thermal energy storage material according to claim 5, wherein: In step S1, the vacuum condition is a vacuum degree ≤ 0.1 MPa.

7. The method for preparing the phase-change composite thermal energy storage material according to claim 5, wherein: In step S2, the stirring temperature is 60-80° C. and the stirring time is 3-5 hours.

8. The method for preparing the phase-change composite thermal energy storage material according to claim 5, wherein: In step S3, the grinding speed is 300-500 rpm and the grinding time is 1-3 hours.

9. The method for preparing the phase-change composite thermal energy storage material according to claim 5, wherein: In step S3, the specific operation of adding in batches is as follows: adding expanded graphite to mixed material A in three batches of 20%, 30% and 50% of the total mass, stirring at a speed of 100-500 rpm for 10-30 minutes after each addition, and adding the next batch after it is fully dispersed.

10. The method for preparing the phase-change composite thermal energy storage material according to claim 5, wherein: In step S4, the cooling rate is 0.5-1.5°C / min, and the temperature is lowered to -10°C to 0°C.

Citation Information

Patent Citations

  • Phase transformation heat accumulating material

    CN101186806A

  • Sodium phosphate dibasic dodecahydrate composite phase change heat storage material and preparation method thereof

    CN115368876A

Cited By

  • Preparation method of composite phase change heat storage module for heat pump system

    CN121064801A